2017 IEEE EMBS International Conference on Biomedical &Amp; Health Informatics (BHI) 2017
DOI: 10.1109/bhi.2017.7897228
|View full text |Cite
|
Sign up to set email alerts
|

A new technique for foot-off and foot contact detection in a gait cycle based on the knee joint angle using microsoft kinect v2

Abstract: The Microsoft Kinect RGB-D sensor has been proven to be a reliable tool for gait analysis and rehabilitation purposes. Although it is accurate for detecting upper body part movements, even the second iteration of the Kinect sensor lacks the accuracy when it comes to lower extremities. while detecting foot-off and foot contact phases of a gait cycle is an important part of a gait performance analysis, The Kinect's intrinsic inaccuracies make it an unreliable tool to detect them accurately. We propose a new Kine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 14 publications
0
18
0
Order By: Relevance
“…To the best of our knowledge, all studies on gait cycle detection using Kinect relied on the first version of the sensor (Kinect v1) [17, 18, 21, 30, 31], with the exception of one that used its second version [38]. In the latter study, the error of estimating gait events/parameters was not reported.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To the best of our knowledge, all studies on gait cycle detection using Kinect relied on the first version of the sensor (Kinect v1) [17, 18, 21, 30, 31], with the exception of one that used its second version [38]. In the latter study, the error of estimating gait events/parameters was not reported.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of gait analysis, different methods for gait cycle detection using the Kinect were proposed [17, 18, 21, 2931, 38]. With the aim of gait rehabilitation in Parkinson’s disease, Cancela et al implemented a finite-state machine that detects different gait cycles phases [29], based on the left and right foot position provided by the first version of the Kinect (Kinect v1).…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, various methods using wearable devices and vision-based systems have been exploited for FOG detection. A number of systems have been proposed with wearable sensors or cameras for FOG detection, including (a) wearable accelerometer and/or gyroscope sensors [2,9,10], (b) smartphone-based sensors [11][12][13], (c) electromyograpy sensors [14,15], (d) pressure/force-based sensors [16,17], and (e) vision-based sensors [18,19]. However, such systems suffer from various drawbacks.…”
mentioning
confidence: 99%
“…The Kinect was found to be a valid tool for assessing spatiotemporal components of gait [5,6] but it is unable to accurately assess lower limb kinematics [7,8]. In order to bypass the lower extremities inaccuracy a technique that relies on knee joint relative angle has been proposed to detect foot-off and foot contact during the gait cycle [9]. The Kinect was successfully used for the classification of human movement during active video game play in relationship to fundamental movement skill [10].…”
Section: Introductionmentioning
confidence: 99%